1988
DOI: 10.1182/blood.v72.2.766.766
|View full text |Cite
|
Sign up to set email alerts
|

Platelet storage: changes in cytosolic Ca2+ actin polymerization and shape

Abstract: Platelets gradually lose their disc shape during storage. The authors studied simultaneous changes in platelet cytosolic Ca2+ (Cai) and the polymerization state of actin as related to the shape. Platelet concentrates were stored under blood bank conditions for up to 10 days. Aliquots were removed and analyzed as follows: platelet Cai and increments in Cai induced by adenosine diphosphate (ADP) were determined by fluorescence of fura-2-loaded cells; loss of disc shape was determined by differences in light scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…There is only limited literature on altered PLT activation in response to physiologic stimuli during storage of PLT concentrates. Some early reports, mostly studying PLTs that were conventionally prepared by pooling PRP, describe changes in basal [Ca 2+ ] i levels and usually transient reduction in agonist‐induced Ca 2+ mobilization during prolonged storage 32‐34 . Differences with the present results may well relate to changes in preparation and processing of the concentrates during the past two decades.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…There is only limited literature on altered PLT activation in response to physiologic stimuli during storage of PLT concentrates. Some early reports, mostly studying PLTs that were conventionally prepared by pooling PRP, describe changes in basal [Ca 2+ ] i levels and usually transient reduction in agonist‐induced Ca 2+ mobilization during prolonged storage 32‐34 . Differences with the present results may well relate to changes in preparation and processing of the concentrates during the past two decades.…”
Section: Discussioncontrasting
confidence: 62%
“…Differences with the present results may well relate to changes in preparation and processing of the concentrates during the past two decades. Thrombin binding to PLTs was also found to decrease during storage, 35 as well as ADP‐ and thrombin‐induced PLT aggregation, 28,36 perhaps because of alterations in cytoskeletal organization and protein tyrosine phosphorylation 33,37 . Together, these reports underscore the present evidence that a major effect of storage is decreased excitability per se of PLTs (owing to senescence?)…”
Section: Discussionsupporting
confidence: 59%
“…Studies of apheresis‐derived PLT concentrates (APCs) revealed an accumulation of soluble P‐selectin, PLT factor 4, CD62P‐positive PLTs, and increasing intracellular Ca 2+ levels . Flow cytometric analysis of PLTs in stored APCs show decreased expression of surface glycoproteins GPIIb/IIIa and GPIb, accompanied by the loss of high‐affinity thrombin receptors on PLT surface .…”
mentioning
confidence: 99%
“…Furthermore, a significant progressive decrease in haemostatic properties occurs, as evidenced by a decreased platelet aggregation response, decreased adenine nucleotide concentration, collection‐ or storage‐induced activation, loss of expression or affinity of surface receptors, activation of complement, and/or a change in the intracellular calcium concentration, leading to a cascade of events promoting platelet activation [6]. The majority of platelets undergo some degree of activation during procurement, processing or storage, leading to in vivo functional compromise [20–24,35].…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions might be mediated by alterations in the biochemical or metabolic activity of the stored platelets, leading to an ultimate compromise in the in vitro function. For instance, irreversible changes in the shape of platelets, elevation of cytosolic calcium, assembly of filamentous actin, loss of activity of enzymes that play a critical role in signal‐transduction events, loss of or decrease in the number of available receptors, or loss of adenylate energy charge, are considered as storage‐induced lesions [19–24]. These lesions, singly or together, will be reflected in the viability and function of a platelet [5,25].…”
Section: Introductionmentioning
confidence: 99%